Design of Y-Shaped Trimers of Chiral Phase-Transfer Catalysts for the Asymmetric Alkylation of Amino Acid Derivatives - Yu, Shengyu; Liu, Jiahao; Wang, Zhe; Kato, Terumasa; Liu, Yan; Maruoka, Keiji (Synlett, 2023)
A series of soluble Y-shaped trimers of chiral phase-transfer catalysts were synthesized and utilized in the asymmetric alkylation of amino acid Schiff bases. The length of the linker between the ammonium cation of the simplified Maruoka catalyst and a phloroglucinol moiety was varied and excellent yields and enantioselectivity were observed when using the Y-shaped trimer of chiral phase-transfer catalyst with an octamethylene linker. A theoretical study of the most efficient Y-shaped trimer of chiral phase-transfer catalyst suggests the chiral ammonium center of the catalyst is more exposed and thus more available in the reaction.
Keywords: Y-shaped trimer; chiral phase-transfer catalyst; asymmetric alkylation; amino acid; theoretical study